Advances in genetic mapping of Septoria nodorum blotch resistance in wheat and applications in resistance breeding - Lin, Min (Burleigh Dodds Series in Agricultural Science, 2021)
Septoria nodorum blotch (SNB) caused by the necrotrophic fungus Parastagonospora nodorum is an important wheat disease in many high rainfall areas across the world. It reduces both yield and grain quality by causing symptoms on wheat leaves and glumes, and can cause yield losses up to 30% under warm and humid conditions. This book chapter gives an update on the recent progress in genetic mapping of SNB resistance in wheat, with focus on adult plant leaf blotch and glume blotch resistance with relevance to resistance breeding. This is followed by a case study on the investigation of the naturally occurring P. nodorum population in Norway and mapping of resistance loci in relevant wheat germplasm using MAGIC populations and GWAS panels as well as how this information can be used to improve resistance breeding and disease management. In the end, some future perspectives of SNB resistance breeding is provided.